A spring-based resonance coupling for hugely enhancing the performance of triboelectric nanogenerators for harvesting low-frequency vibration energy. (February 2017) - Wu, Changsheng; Liu, Ruiyuan; Wang, Jie; Zi, Yunlong; Lin, Long; Wang, Zhong Lin
Abstract: Low-frequency vibration is a ubiquitous energy that exists almost everywhere, but a high efficient harvesting of which remains challenging. Recently developed triboelectric nanogenerator (TENG) provides a promising alternative approach to conventional electromagnetic and piezoelectric generators, with the advantage of low cost and high output voltage. In this work, a mechanical spring-based amplifier with the ability of amplifying both the vibration frequency and amplitude is integrated with TENG to improve its low-frequency performance by up to 10 times. A new scheme for evaluating TENG using the average output power is proposed and the process of choosing an appropriate time interval for analysis is demonstrated. It takes into account the temporal variation in electrical output and offers a more accurate and convincing evaluation of TENG's performance in practical working environment compared to previously used instantaneous power. This work serves as an important progress for the future development and standardization of TENG, especially for harvesting low-frequency vibration energy as well as a great prospect of blue energy. Graphical abstract: Highlights: Integration of mechanical amplifier with conventional triboelectric nanogenerator. A coupled-spring structure to store mechanical kinetic energy and potential energy. Amplification of vibration frequency and amplitude of the active elements in TENGs. A performance boost of up to 10 times in average output power. A new performance evaluation scheme for TENGs in practical working environment.